2021
DOI: 10.3390/nu13041108
|View full text |Cite
|
Sign up to set email alerts
|

Gluten-Free Diet: Nutritional Strategies to Improve Eating Habits in Children with Celiac Disease: A Prospective, Single-arm Intervention Study

Abstract: Background: Elimination of gluten-containing cereals and consumption of ultra-processed gluten-free foods might cause an unbalanced diet, deficient in fiber and rich in sugar and fat, circumstances that may predispose celiac children to chronic constipation. Aim: to evaluate if counseling with a registered dietitian (RD) was capable of improving eating and bowel habits in a celiac pediatric population. Methods: Dietetic, lipid profile and stool modifications were analyzed, comparing baseline assessments with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 66 publications
0
5
0
1
Order By: Relevance
“…Furthermore, considering the presence of gluten-free products as a source of UPF in the diets of people with CD, it should also be relevant to promote the consumption of naturally gluten-free cereals to improve the diet quality of people with CD. In fact, some studies have already demonstrated the efficacy of nutrition education in people with CD, reporting an improvement in UPF consumption and better adherence to MD in children, adolescents [ 15 , 33 ], and adults [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, considering the presence of gluten-free products as a source of UPF in the diets of people with CD, it should also be relevant to promote the consumption of naturally gluten-free cereals to improve the diet quality of people with CD. In fact, some studies have already demonstrated the efficacy of nutrition education in people with CD, reporting an improvement in UPF consumption and better adherence to MD in children, adolescents [ 15 , 33 ], and adults [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients educated by a dietitian are more likely to make healthier food choices 110 . In a recent intervention study on 72 children, there were significant improvements in their dietary habits when educated by a dietitian, with lower intakes of sugar and ultra‐processed foods and overall increase of fruits and fiber 111 Thus, nutrition education of patients and their families by a dietitian may improve nutritional and health status.…”
Section: Resultsmentioning
confidence: 99%
“…As the GFD is complex and requires several skills in nutrition, food labeling, adaption to family food culture, a clinical dietitian trained in CD is recommended to give both the first as well as the continued education on the GFD. 42,115 The dietitian supports the adherence to the GFD, 116 adherence to healthier dietary habits, 111 is safe and cost effective in the follow-up care, 117 and patients appreciate the contact with the dietitian. 118 Monitoring patients with both type 1 diabetes and CD is particularly challenging.…”
Section: Whomentioning
confidence: 99%
“…So far, nutrition education about CD and diet has been focused on people suffering from CD [43][44][45][46][47] as it is necessary to improve their health and quality of life. Nevertheless, nutrition education should go beyond the patient, since family members and social environments also have an influence on the management of the disease, as previous studies have shown [48][49][50][51][52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%